Working capital management: strategic techniques and choices - "Chadamiya, Bhavesh. P"; Menapara, Mital R. (New Delhi, 2013)
Globalisation is widely seen as the most important factor that could influence economies of nations the world over in the new millennium. The rapid advancement in information technology and communications has made it not just possible but absolutely essential for industry the world over to adapt or fall by the wayside. The issue that concerns developing countries is how one can ensure greater participation of the weaker economies, particularly backward regions of these economies, in the global process and what needs to be done to ensure that the course of globalisation benefits more people in more countries. The socio-economically disadvantaged are yet to benefit from reform policies. The challenge to overcome the scourge of poverty remains a daunting task. This book analyses the trend towards globalisation and focuses on implications of it for backward regions of India.
Keywords: "Working capital management, Capital"